2021
DOI: 10.1140/epjp/s13360-021-01119-2
|View full text |Cite
|
Sign up to set email alerts
|

Black hole shadow to probe modified gravity

Abstract: We study the black hole's shadow for Schwarzschild-de Sitter and Kerr-de Sitter metrics with the contribution of the cosmological constant Λ. Based on the reported parameters of the M87* black hole shadow, we obtain constraints for the Λ and show the agreement with the cosmological data. It is shown that the coupling of the Λ-term with the spin parameter reveals peculiarities for the photon spheres and hence for the shadows. Within the parametrized post-Newtonian formalism, the constraint for the corresponding… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(11 citation statements)
references
References 21 publications
(15 reference statements)
2
9
0
Order By: Relevance
“…Figure 9 is representative, however, of a black hole with mass M, with which one can adjust the range of Λ suitably. Considering the M87* as a new Kerr-de Sitter black hole, and using the mass M = 6.5 × 10 9 M and distance d = 16.8 Mpc as reported by the Event Horizon Telescope collaboration (EHT) [85][86][87], we estimate the value of the cosmological constant Λ = 1.046 × 10 −52 m −2 , 1.368 × 10 −52 m −2 obtained, respectively, for (R s , δ s )= (4.985 × 10 13 m, 0.5) and (A, D)= (7.298 × 10 27 m 2 , 0.9812), which agree with the present estimated value of Λ = 1.11 × 10 −52 m −2 [88][89][90]. Thus, our method is robust to estimate the cosmological constant Λ as well as the spin a, provided one has a suitably chosen range for a given black hole.…”
Section: Parameter Estimation and Relative Difference Of Shadow Obser...supporting
confidence: 91%
“…Figure 9 is representative, however, of a black hole with mass M, with which one can adjust the range of Λ suitably. Considering the M87* as a new Kerr-de Sitter black hole, and using the mass M = 6.5 × 10 9 M and distance d = 16.8 Mpc as reported by the Event Horizon Telescope collaboration (EHT) [85][86][87], we estimate the value of the cosmological constant Λ = 1.046 × 10 −52 m −2 , 1.368 × 10 −52 m −2 obtained, respectively, for (R s , δ s )= (4.985 × 10 13 m, 0.5) and (A, D)= (7.298 × 10 27 m 2 , 0.9812), which agree with the present estimated value of Λ = 1.11 × 10 −52 m −2 [88][89][90]. Thus, our method is robust to estimate the cosmological constant Λ as well as the spin a, provided one has a suitably chosen range for a given black hole.…”
Section: Parameter Estimation and Relative Difference Of Shadow Obser...supporting
confidence: 91%
“…For a non-Kerr rotating black hole whose null geodesic equations is integrable, the black hole shadow can also be obtained in the same way for the calculation (10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25) of Kerr black hole shadow. P. V. P. Cunha et al [10] studied the shadow of a Kerr black hole with Proca hair [10], and found black hole shadow has a cusp silhouette, shown in Fig.…”
Section: B Fundamental Photon Orbitsmentioning
confidence: 97%
“…For example, it is a perfect black disk for Schwarzschild black hole shadow; it gradually becomes a "D"-shaped silhouette with the increase of spin parameter for Kerr black hole shadow [8,9]; it is a cusp shadow for a Kerr black hole with Proca hair [10] and a Konoplya-Zhidenko rotating non-Kerr black hole [11]. The research of black hole shadows plays a vital role in the study of black holes (constraining black hole parameters) [12,13], probing some fundamental physics issues including dark matter [14][15][16] and verification of various gravity theories [17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…The fourth and fifth column on the other hand are values we have computed using celestial coordinates in Ref. [1], We have chosen Λ = 1.11 × 10 −52 m −2 because cosmological tests and CMB measurements imply that this is the relevant value of the cosmological constant [27], [28], [29] TABLE II: Points evaluated for θ = 16 eq. ( 65)-( 66).…”
Section: Horizontal Diameter ∆α = (αmentioning
confidence: 99%